2012 IEEE International Energy Conference and Exhibition (ENERGYCON) 2012
DOI: 10.1109/energycon.2012.6347757
|View full text |Cite
|
Sign up to set email alerts
|

New type of power converter for common-ground DC bus sharing to increase the energy efficiency in drive systems

Abstract: This paper proposes a new type of power converter for drive systems to enable the exchange of recuperated energy within an independent DC subgrid having one centralized energy storage element.Many industrial applications that require rapid cyclic starts and stops are subject to significant energy waste at the brake chopper of the DC bus due to over voltage during motor deceleration. The proposed solution allows the brake chopper to be eliminated and the otherwise wasted energy to be stored externally. The solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Another research that uses energy-efficient motion planning method can be found in [22,23]. In their research, they discovered a solution for reducing the energy consumption of IR by optimizing their motion planning without changing system configurations.…”
Section: Developing Energy-efficient Motion Planningmentioning
confidence: 99%
“…Another research that uses energy-efficient motion planning method can be found in [22,23]. In their research, they discovered a solution for reducing the energy consumption of IR by optimizing their motion planning without changing system configurations.…”
Section: Developing Energy-efficient Motion Planningmentioning
confidence: 99%
“…In most cases, if several axes brake at the same time, the available energy exceeds the installed DC-bus capacitance. Thus, the energy is dissipated on a balancing or chopper resistor [30]. By properly designing and adding the number of storing devices, this energy can be almost fully recovered and then shared.…”
Section: Energy-sharing Devicesmentioning
confidence: 99%
“…The EnergyTeam is a promising solution, but it requires a robot controller able to receive external DC power. In [30][31][32], the case of a single centralized capacitor that is shared between different DC subgrids (i.e., a subgrid is composed by several drive systems), each one with its own rectifier, is considered. In these papers, a method to avoid the synchronization between every rectifier's subgrids is proposed.…”
Section: Energy-sharing Devicesmentioning
confidence: 99%
See 2 more Smart Citations